The Foreign Corrupt Practices Act's Consquences for U.S. Trade: The Nigerian Example - Geo-Jala, Macleans A. (Journal of business ethics, 2000)
A by-product of the Watergate investigations into illegal political contributions and money-laundering was the revelation that American corporations had been making questionable payments to foreign officials to gain business advantages. That discovery was the driving force behind passage of the FCPA in 1977. Many since have complained that the law put American firms at a disadvantage in international trade. This paper assesses the credibility of that claim, as well as exploring the socioeconomic implications of corruption in a world of intensifying international competition. Based on the literature review, examination of international trade data and intensive interviews with foreign firms doing business in Nigeria, the paper reaches the following conclusions:, 1. Enforcement of FCPA has waxed and waned, but there is no evidence that its enforcement has impeded the growth of U.S. trade. In fact, trade with countries previously considered "bribe prone" has out-paced the growth of trade with non-bribe-prone countries, despite FCPA., 2. Those American corporations which, in the past, were guilty of international bribery did so as a short-cut when adherence to time-honored ethics could have accomplished the same or better results., 3. The "Storehouse of Knowledge" maintained by successful firms has been far more influential in promoting exports than any questionable payments they might be tempted to make., 4. In most of the questionable payments investigated, American corporations had indulged in bribery to gain a competitive edge over other U.S. firms rather than foreign ones., 5. Whatever the result, international bribery is inherently wrong for the same reason that domestic bribery is wrong., Despite criticism of it, FCPA has benefitted honest U.S. firms by reducing unfair competition among other American firms which comprise about 80 percent of the world's true multinationals. For multinationals to function in anything other than a transparent manner would be to impede the spread of democratic governments and market economies worldwide.